2017
DOI: 10.15406/mojwh.2017.04.00079
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Modified Triple-P Method with Adherent Placenta Long - Term Results

Abstract: At the article we represent the long-term results in 17 women who were operated using the modified technique of the Triple-P procedure with placenta percreta. Research was conducted with help of a specially designed questionnaire for patients and ultrasound examination of the wall uterus, especially of the anterior wall and the edge of postoperative scar. System analysis of literature data on this problem was conducted. preterm delivery before 37 weeks amounted to 82.4% (n=14). There were no cases of perinatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…The authors reported good outcomes and this modified procedure may be useful in centers with no access to interventional radiology . The same authors have subsequently performed 35 surgeries using this procedure and have reported good long‐term outcomes at 24 months after surgery …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors reported good outcomes and this modified procedure may be useful in centers with no access to interventional radiology . The same authors have subsequently performed 35 surgeries using this procedure and have reported good long‐term outcomes at 24 months after surgery …”
Section: Discussionmentioning
confidence: 99%
“…19 The same authors have subsequently performed 35 surgeries using this procedure and have reported good long-term outcomes at 24 months after surgery. 20 More recently, a Chinese case series of 45 patients managed using the modified Triple P Procedure applied uterine strangulation instead of pelvic arterial balloon occlusion, with good outcomes 21 and a comparable mean blood loss of 2423 mL 21 and 1078 mL, 19 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A study from 25 USA hospitals found that the average blood loss was 2000 ml [12]. The amount of blood loss reported from the modified triple P approach was 1440 ml [9]. There are many factors affecting the calculated amount of blood loss other than the accuracy of the method of calculation.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the success rate was 84.3% using internal iliac artery ligation combined with endosutures in 38 patients [17]. Using the modified triple P approach in 35 patients achieved success rate of 85.7% [9]. A stepwise approach including multiple steps in 65 patients avoid hysterectomy in 91.5% [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation